الشخصية والعوامل الاجتماعية عند إيرك فروم دراسة تحليله - عمران هاني; الشعار مصطفى (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
Eric Fromm presented a theory in human personality launched based on the community and social environment. It can be said that this theory came in the context of his critical reviews to the theory of psychoanalysis, which gave the unconscious and instincts the biggest role in the formation of human personality. The current research has taken the social factor and its role in the synthesis of personality (according to Fromm) a subject for analysis to determine the following points: The element of social personality and its ingredients at Fromm framework and the dynamic nature between the individual and the society Personality building according to Fromm قدم إيرك فروم نظرية في الشخصية الإنسانية انطلق فيها من المجتمع والمحيط الاجتماعي، ويمكن القول أن نظريته تلك إنما جاءت في سياق مراجعاته النقدية لنظرية التحليل النفسي التي أولت اللاشعور والغرائز الدور الأكبر في تركيب الشخصية الإنسانية، وقد اتخذ البحث الحالي من العامل الاجتماعي ودوره في تركيب الشخصية عند فروم موضوعاً للتحليل للوقوف على النقاط التالية: عناصر الشخصية الاجتماعية ومكوناتها عند ايرك فروم جدلية الشخصية الاجتماعية في إطار اجتماعي-اقتصادي و دينامية العلاقة بين الفرد والمجتمع بناء الشخصية عند فروم